Rainfall Features and Agricultural Droughts at Agra - Prajapati, M C; Agrawal, M C; Bhaskar, K S (Annals of Arid Zone, 2016)
At the soil Conservation Research Station, Chhalesar (Agra) the length of normal wet season is 21 weeks from IV week of May to III week of October in which the ratio of wet and dry rainfall weeks is of 5: 6. The probability of deficient rainfall (33 to 60 percent) and coefficient of variability of rainfall (67 to 122 percent) are lowest and occurrence chances of rainfall (67 to 100 percent) are highest during IV wed.: of June to II week of September making it the most dependable period for raising rainfed crops. Normally a period of 11.5 weeks or 54.76 percent of the wet season is eclipsed by droughts. Three out of four years suffer from early droughts but only one from serious one. There are two to five mid season droughts involving 4 to 11 weeks which prove to be highly detrimental to the crops. The late droughts occur in 80 percent cases half of them being of four or five weeks duration resulting into failure of otherwise promising kharif crops. Normally a rainfed kharif crop at Agra is destined to invariably face droughts during the course of its growth period. The inferences can be generalised if a hundred year data arc utilized for the review